2022
DOI: 10.1186/s12967-022-03492-7
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of human microbiome in cancer development and response to therapy: special focus on intestinal microflora

Abstract: In recent years, there has been a greater emphasis on the impact of microbial populations inhabiting the gastrointestinal tract on human health and disease. According to the involvement of microbiota in modulating physiological processes (such as immune system development, vitamins synthesis, pathogen displacement, and nutrient uptake), any alteration in its composition and diversity (i.e., dysbiosis) has been linked to a variety of pathologies, including cancer. In this bidirectional relationship, colonizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 255 publications
0
48
0
Order By: Relevance
“…The compositional and functional disequilibrium of the gut ecosystem, known as dysbiosis, is accountable for the disclosure of several diseases from neurological affections [ 130 , 131 ], to the liver [ 132 ], cardiovascular [ 133 ], autoimmune diseases [ 134 ], food allergies [ 135 ], diabetes [ 136 ], obesity [ 137 ], cancer development [ 138 ], decreased calcium absorption [ 139 ], and even influence the severity of infectious disease such as COVID-19 [ 140 , 141 ]. The applicability of these compounds can exert an alleged “prebiotic” outcome on the health of humans and animals.…”
Section: Health Benefits Of Pegsmentioning
confidence: 99%
“…The compositional and functional disequilibrium of the gut ecosystem, known as dysbiosis, is accountable for the disclosure of several diseases from neurological affections [ 130 , 131 ], to the liver [ 132 ], cardiovascular [ 133 ], autoimmune diseases [ 134 ], food allergies [ 135 ], diabetes [ 136 ], obesity [ 137 ], cancer development [ 138 ], decreased calcium absorption [ 139 ], and even influence the severity of infectious disease such as COVID-19 [ 140 , 141 ]. The applicability of these compounds can exert an alleged “prebiotic” outcome on the health of humans and animals.…”
Section: Health Benefits Of Pegsmentioning
confidence: 99%
“…The GM is a potential controller of wellness and disease. As demonstrated by experimental, clinical, and epidemiological evidence, a dysbiotic microbiota (i.e., a microbiota that deviates from the “eubiotic” status in terms of diversity and functionality [ 11 ]) is implicated in a range of diseases in adults, including inflammatory bowel disease [ 12 , 13 ], arthritis [ 14 ], cancer [ 15 ], neurological and neuropsychiatric disorders [ 16 ], cardiometabolic [ 17 ] and cardiovascular [ 18 ] disease, obesity [ 19 ], type 2 diabetes [ 20 , 21 , 22 ], and, as detailed below, infertility.…”
Section: Gut Microbiota: a New Player In Townmentioning
confidence: 99%
“…Many studies report an existing relationship between the gut microbiome and human cancer development, including brain tumours. 157 - 159 Animal models demonstrated that gut microbiome-driven changes to microglia in the CNS have a direct impact on CNS disease. 160 Such changes are either direct or indirect.…”
Section: Brain Tumor Pathogenesismentioning
confidence: 99%